Cytogenetics and molecular cytogenetics in diffuse large B-cell lymphoma (DLBCL) - Nedomova, Radka; Papajik, Tomas; Prochazka, Vit; Indrak, Karel; Jarosova, Marie (Biomedical papers, 2013)
Background: Diffuse large B-cell lymphoma (DLBCL) accounts for up to 40% of all non-Hodgkin's lymphomas diagnosed in the western hemisphere. Determination of the gene expression profile has confirmed the physiological heterogeneity of the disease and defined three molecular prognostic subgroups - germinal center B-cell-like (GCB), activated B-cell-like (ABC) and primary mediastinal B-cell lymphoma (PMBL) - with different gene expression and prognosis.Methods and Results: This review covers current knowledge on the most frequent recurrent cytogenetic and molecular cytogenetic aberrations in molecular DLBCL subgroups.Conclusions: Cytogenetic and molecular cytogenetic techniques used to determine nonrandom chromosomal aberrations in patients with DLBCL have revealed the incidence of frequent cytogenetic aberrations in the subgroups reported, suggesting their potential use for more accurate prognostic stratification of DLBCL, contributing to personalized selection of the most effective therapy.
Keywords: diffuse large B-cell lymphoma; prognostic subgroups; chromosomal aberrations; molecular cytogenetics; arrayCGH